1999
DOI: 10.1034/j.1399-5618.1999.10111.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate as add‐on treatment for patients with bipolar mania

Abstract: Topiramate appears to have efficacy for the manic and mixed phases of bipolar illness. Other preliminary data suggest antidepressant efficacy too. Among obese bipolar subjects, the weight loss potential of topiramate may be beneficial. If controlled trials confirm these initial results, topiramate may be a significant addition to the available treatments for bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 24 publications
(43 reference statements)
5
82
1
1
Order By: Relevance
“…In laboratory studies, TPM blocked the effects of kainite-induced excitatory conductance in cultured rat hippocampal neurons (Gibbs et al, 2000), and reduced the effects of hippocampal neuronal damage in gerbils caused by ischemia (Lee et al, 2000). These and other preclinical findings have provided a putative mechanism for the effects of TPM as an anticonvulsant (Jahromi et al, 2000;Shank et al, 2000), and are consistent with some clinical reports of the antiepileptic effects and mood-stabilizing effects of this compound (Chengappa et al, 1999;Jette et al, 2002;Privitera et al, 2003).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In laboratory studies, TPM blocked the effects of kainite-induced excitatory conductance in cultured rat hippocampal neurons (Gibbs et al, 2000), and reduced the effects of hippocampal neuronal damage in gerbils caused by ischemia (Lee et al, 2000). These and other preclinical findings have provided a putative mechanism for the effects of TPM as an anticonvulsant (Jahromi et al, 2000;Shank et al, 2000), and are consistent with some clinical reports of the antiepileptic effects and mood-stabilizing effects of this compound (Chengappa et al, 1999;Jette et al, 2002;Privitera et al, 2003).…”
Section: Introductionsupporting
confidence: 79%
“…Diminished GR sensitivity has been associated with MDD (for a review see Pariante and Miller, 2001). That TPM might increase the sensitivity of GR is consistent with observed effects of this compound in mood disorders (Chengappa et al, 1999;Grunze et al, 2001;Carpenter et al, 2002). On the other hand, in some subjects, primarily those with PTSD whose pretreatment lysozyme IC 50 values were relatively low, TPM had the effect of reducing the sensitivity of the receptor, similar to what was observed in rats who demonstrated decreased mRNA expression following treatment with TPM.…”
Section: Discussionsupporting
confidence: 57%
“…Topiramate is a currently marketed antiepileptic agent that has been shown to cause weight loss and improve insulin sensitivity in both humans (4,13) and animals (12,14). Our own studies have shown that Topiramate treatment in insulin-resistant female ZDF rats can lead to amelioration of insulin resistance independently of weight loss.…”
Section: Discussionmentioning
confidence: 91%
“…[63][64][65][66] Rigorously performed, controlled trials, however, failed to find any benefit from use of this drug in bipolar disorder. 67 Topiramate has been commonly prescribed for patients with bipolar disorder, not only because of the expectation that it will prove to be efficacious, but also because of its weight-reducing effects, which are felt to be particularly desirable to counteract the weight gain induced by some other mood stabilizing agents (e.g., valproic acid).…”
Section: Topiramatementioning
confidence: 99%